Lay participation in criminal trials: a comparative perspective - Ma, Yue (International criminal justice review, 1998)
The institution of lay participation in criminal matters has undergone dramatic changes on the world scene during the twentieth century. Today, the common law jury trial flourishes only in the United States. Critics contend that overreliance on the lay jury as the sole fact finder hinders rather than facilitates the prompt and fair adjudication of guilt. This article examines the lay participation systems in some major countries and compares their characteristics with that of our own